Political System Influences within the Indonesian Islamic Da’wah Institute (LDII) and the Egyptian Muslim Brotherhood (IM) - Hilmi Muhammadiyah; Muhammed Sahrin Bin Haji Masri (Al-Albab, 2025)
This article examines the dynamic interactions between religious movements and state authorities by comparing two distinct Islamic organizations: the Indonesian Islamic Da’wah Institute (Lembaga Dakwah Islam Indonesia, LDII) in Indonesia and the Muslim Brotherhood (Ikhwanul Muslimin, IM) in Egypt. Both organizations, rooted in Islamic principles, have forged complex relationships with their respective states, yet their paths reflect divergent approaches shaped by unique national contexts. LDII, operating within Indonesia’s pluralistic democracy, which Pancasila underpins, has strategically adapted to national norms. Despite past controversies, LDII has embraced a pragmatic approach, emphasizing Quran and Hadith-based teachings, actively participating in socio-economic initiatives, formalizing its organizational structure, and collaborating with government programs. This demonstrates a flexible alignment with Indonesia’s emphasis on national unity and religious moderation. In stark contrast, Egypt’s Muslim Brotherhood, once a dominant political force, faced an existential threat following the 2013 military coup. Forced into exile, the IM has largely maintained an ideologically rigid stance in opposition to the state. By analyzing these two cases, this study highlights how contextual factors, ranging from political systems and state ideologies to historical trajectories and internal organizational dynamics, profoundly shape the strategies employed by religious movements to survive and thrive within state-religion frameworks.